Wind-driven ventilation improvement with plan typology alteration: a CFD case study of traditional Turkish architecture - Aydin, Yusuf Cihat; Mirzaei, Parham A. (Springer, 2016)
Aligned with achieving the goal of net-zero buildings, the implementation of energy-saving techniques in minimizing energy demands is proving more vital than at any time. As practical and economic options, passive strategies in ventilation developed over thousands of years have shown great potential for the reduction of residential energy demands, which are often underestimated in modern building’s construction. In particular, as a cost-effective passive strategy, wind-driven ventilation via windows has huge potential in the enhancement of the indoor air quality (IAQ) of buildings while simultaneously reducing their cooling load. This study aims to investigate the functionality and applicability of a common historical Turkish architectural element called “Cumba” to improve the wind-driven ventilation in modern buildings. A case study building with an archetypal plan and parameters was defined as a result of a survey over 111 existing traditional samples across Turkey. Buildings with and without Cumba were compared in different scenarios by the development of a validated CFD microclimate model. The results of simulations clearly demonstrate that Cumba can enhance the room’s ventilation rate by more than two times while harvesting wind from different directions. It was also found that a flexible window opening strategy can help to increase the mean ventilation rate by 276%. Moreover, the room’s mean air velocity and ventilation rate could be adjusted to a broad range of values with the existence of Cumba. Thus, this study presents important findings about the importance of plan typology in the effectiveness of wind-driven ventilation strategies in modern dwellings.